Pitfalls, challenges and caveats in whole mitochondrial genome sequencing from hair shafts by MPS: Where, when and how to address them. (December 2022) - Turchi, Chiara; Melchionda, Filomena; Alessandrini, Federica; Onofri, Valerio; Pesaresi, Mauro; Buscemi, Loredana; Tagliabracci, Adriano
Abstract: The growing use of massively parallel sequencing (MPS) for the whole mitochondrial genome analysis in forensic laboratories, requires the establishment of efficient workﬂows and interpretation procedures, to support the feasibility of the technology and the reliability of the data. In the case of reference samples, such as blood and buccal swabs, the generation of mtDNA profiles by using MPS is relatively simple. Conversely, many forensic casework samples still pose challenges for the MPS, data interpretation and reporting of mtDNA. This is especially true for the analysis of shed hairs, which are one of the most common evidence types and which are among the most limited in terms of DNA quantity and quality. Due to these limitations, every step involved in the analysis become essentials and should be performed in order to obtain the best performance, optimizing the outcomes and minimizing the errors. In light of this, we present a study focusing on the extraction, quantification and MPS of the whole mtDNA in hair shafts, with the aims of set-up and validate a methodological pipeline to obtain the best sequencing results. The overall performance of the MPS panel, mainly in terms of total coverage, amplicons coverage and different primer pools efficiency, was evaluated also in relation to the different hair fragments, the mtDNA copy number used for libraries preparation and its degradation state.